1994
DOI: 10.1577/1548-8659(1994)123<0080:ldwsal>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Length-Dependent Winter Survival and Lipid Composition of Age-0 Largemouth Bass in Bay Springs Reservoir, Mississippi

Abstract: Age-0 largemouth bass Micropterus salmoides were studied in Bay Springs Reservoir, Mississippi, to determine if the larger young had greater survival through their first winter and if this survival was influenced by levels of energy reserves. Abundance decreased from 542 young/ hectare in June, when fish averaged 37 mm total length, to 12/hectare in March, when lengths averaged 149 mm. The length-frequency distribution of this year-class was positively skewed during June-August, became bimodal during September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
122
4
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 18 publications
13
122
4
2
Order By: Relevance
“…4,8) Over-winter survival is lipid-dependent as reported in some freshwater fish. [17][18][19] Decrease of water temperature causes an activation of hepatic dehydrogenases such as G6PDH and PGDH which coincide with an increase in lipid contents.20,21) In our study, increases in lipogenic enzyme activity in au tumn suggested active lipid accumulation toward winter.…”
Section: Discussionsupporting
confidence: 51%
“…4,8) Over-winter survival is lipid-dependent as reported in some freshwater fish. [17][18][19] Decrease of water temperature causes an activation of hepatic dehydrogenases such as G6PDH and PGDH which coincide with an increase in lipid contents.20,21) In our study, increases in lipogenic enzyme activity in au tumn suggested active lipid accumulation toward winter.…”
Section: Discussionsupporting
confidence: 51%
“…Differences were probably due to interspecific variation in winter habitat use, encounter rates, or subtle differences in gape size (sensu Micucci et al 2003). Although the ponds are generally homogeneous, piscine prey may partition habitats spatially (Miranda & Hubbard 1994) and exhibit temporal variation in habitat use or activity patterns. Although little is known about winter activity of bluegill some typically diurnal fish including minnows become nocturnal at low temperatures Three of the nine ponds had bluegill and macroinvertebrates, three ponds had fathead minnows and macroinvertebrates, and the remaining three ponds had only macroinvertebrates as available forage for age-0 largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
“…For many piscivorous fish, subtle differences in the timing of hatching of eggs may determine whether gape-limited juveniles grow sufficiently large to consume piscine prey, increase their energy intake, grow rapidly, and reach large fall size (Adams and DeAngelis 1987, Goodgame andMiranda 1993, Phillips et al 1995). Because large size as a function of early interactions often increases the probability of winter survival in temperate-latitude fish (Post and Evans 1989, Miranda and Hubbard 1994, Garvey et al 1998c) and amphibians (Dratnal andDavies 1990, Jiang andClaussen 1992), interactions among life stages and their consequences for first-year growth have important implications for recruitment to reproductive age.…”
Section: Introductionmentioning
confidence: 99%